Analysis of Impacts of Electrical Architectures, Social-Economic Considerations and Regions, on Requirements for Residential Combined Solar and Battery Implementations - (:unkn) unknown (My University, 2018)
A community DC MG in an urban environment is analyzed and aimed at driving down the utility costs in a low-income household. A typical home conventional AC loads is compared with smart technologies to prove that utility bills can be significantly reduced. The optimal installation and usage of solar and battery energy storage is determined for the entire integrated community aiming to achieve net zero energy community. This study revealed a need for better understanding of the loads in each house and load patterns across a wide range of regions nationally and more typical houses, as opposed to the specialized study of the Milwaukee DC microgrid. As a result, current research also incorporates analysis of different architectures, for the Residential Microgrid modeling, for different types of homes in five different locations to contemplate theoretical and statistical understanding of suitable architecture. Critical AC loads are identified, and came up with an equivalent replacement for the DC Loads. Loads which are continually in use are taken into consideration, such as DC LED lights, Electronic Loads, Air Conditioner’s/Heat Pumps. So, proposed methods and systems cost less for an average home owner, than the one proposed by NREL Study for Installed Cost Benchmarks for Residential Solar Photovoltaics with Energy Storage.